2019
DOI: 10.1177/1948550619845927
|View full text |Cite
|
Sign up to set email alerts
|

Actual and Perceived Emotional Similarity in Couples’ Daily Lives

Abstract: We used two experience sampling studies to examine whether close romantic partners’ feelings of love and perceived partner responsiveness are better predicted by their actual emotional similarity or by their perceived emotional similarity. Study 1 revealed that the more partners were emotionally similar, the more they perceived their partner as responsive. This effect was mediated by perceived similarity, indicating that emotional similarity had to be detected in order to exert an effect. Further, when people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 60 publications
5
32
0
Order By: Relevance
“…Communal motives refer to the importance that individuals place on feeling understood, supported, and welcomed by others (instead of concealed, shielded, and insulated from others) in interpersonal situations and relationships (Locke, 2000(Locke, , 2018. Because perceived selfother similarity can help satisfy communal motives (e.g., Hampton et al, 2019;Montoya et al, 2008;Sels et al, 2020), individuals with stronger communal motives may be more motivated to perceive self and others as similar. Indeed, several studies have found that stronger communal motives towards others predicted greater similarity between self-ratings of personality traits and ratings of the traits of liked or ingroup others (Locke et al, 2012;Locke & Christensen, 2007).…”
Section: Communal Motives and Perceived Similaritymentioning
confidence: 99%
See 1 more Smart Citation
“…Communal motives refer to the importance that individuals place on feeling understood, supported, and welcomed by others (instead of concealed, shielded, and insulated from others) in interpersonal situations and relationships (Locke, 2000(Locke, , 2018. Because perceived selfother similarity can help satisfy communal motives (e.g., Hampton et al, 2019;Montoya et al, 2008;Sels et al, 2020), individuals with stronger communal motives may be more motivated to perceive self and others as similar. Indeed, several studies have found that stronger communal motives towards others predicted greater similarity between self-ratings of personality traits and ratings of the traits of liked or ingroup others (Locke et al, 2012;Locke & Christensen, 2007).…”
Section: Communal Motives and Perceived Similaritymentioning
confidence: 99%
“…Greater perceived similarity with another person contributes to liking and attraction (Montoya et al, 2008;Selfhout et al, 2009) and expecting that other person to like you (Hampton et al, 2019). In romantic relationships, perceived similarity contributes to feelings of love and relationship satisfaction (Murray et al, 2002;Sels et al, 2020). Because perceived similarity can have important consequences, it is important to understand the variables that contribute to perceived similarity.…”
mentioning
confidence: 99%
“…Thus, we argue that experiencing a similar outlook on the world contributes to the development of shared reality, an important component of couple identity (Echterhoff, Higgins, & Levine, 2009;Rossignac-Milon, Bolger, Zee, Boothby, & Higgins, in press) and our interpersonal chemistry model (see cognitive element of perceived chemistry in Figure 1). Research routinely shows that people perceive higher levels of similarity than actually exists in their positive relationships-for example, believing one's friends are just as progressive or conservative as oneself, when they are not (e.g., de Jong & Reis, 2014;Goel, Mason, & Watts, 2010;Sels, Ruan et al 2020), and, as we discuss later, at least some of this overperception involves projection of one's own attitudes and preferences onto the other (Morry, 2005). Because we believe perceived chemistry reflects perceptions of a match between oneself and a partner, and notwithstanding the likelihood that perceived similarity is based on some level of actual similarity, it is useful to conceptualize the cognitive element of chemistry in terms of perceived similarity over and above actual similarity.…”
Section: Perception Of Shared Identitymentioning
confidence: 99%
“…For these reasons, we considered fast, valid, and reliable self-reporting measures were necessary to assess the social interdependence used to configure and improve couple relationships [ 28 , 29 ]. In this sense, the present study deepens the understanding of such interdependence and how it impacts a couple’s regulation of their emotional life [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 95%